Relationship between Toluene Concentration, Malondialdehyde (MDA) Level and Health Complaints in Workers of Surabaya Printing Industry - Pradita Sekar Ayu1 , Abdul Rohim Tualeka2 , Shintia Yunita Arini3 , Syamsiar S Russeng4 , Pudji Rahm (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Toluene is one of the chemical compounds used in the production process in the printingindustry. Exposure toluene that exceeds the threshold value continuously can result in increased levels ofmalondialdehyde and the possibility of experiencing various health complaints. The purpose of this studywas to determine the relationship between toluene concentrations, malondialdehyde levels and healthcomplaints in workers at X Surabaya printing.Methods: This research is observational with quantitative approach and cross sectional design. The studywas conducted on workers in X Surabaya printing. The number of respondents in this study were 19 people.The variables studied were toluene concentration, malondialdehyde levels, and health complaints. Data wereanalyzed using Pearson correlation test.Result: The average concentration of toluene was 1.2311 ppm and the average concentration ofmalondialdehyde was 8,323 MU. Pearson correlation test results showed the relationship of tolueneconcentration with malondialdehyde obtained p value = 0.508 (p> 0.05). While the results of healthcomplaints that were most experienced were coughing (74%), headaches (63%) and shortness of breath(26%).Conclusion: There is no significant relationship between toluene concentration and malondialdehyde level.While the most commonly experienced health complaints are coughing, headaches, and shortness of breath.